2021
DOI: 10.54589/aol.34/1/050
|View full text |Cite
|
Sign up to set email alerts
|

Micro-computed tomographic evaluation of root canal morphology in mandibular first premolars from a Colombian population

Abstract: Dental anatomy can vary significantly between different populations from different countries. Dental anatomical variations are of great interest to the dental professional, especially to endodontists, since they can influence the outcome of endodontic treatment. The purpose of the present study was to describe the anatomical variations of the root canal in mandibular first premolars in a population from Colombia, using micro-computed tomography. Fifty mandibular first premolars were scanned on a SkyScan 1174 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
3
0
4
Order By: Relevance
“…However, lingual view showed 73% of canals in the middle third and remaining in the coronal third In proximal view, mean angle α and β were 33.54∘ and 26.66∘ and angles were extremely curved while in the lingual view, they were less curved with mean angle α 8.31∘ and β 11.31∘ respectively _ _ _ _ _ _ _ The study provided the details of lingual canal, however the information obtained was influenced by the view used Liu, N., et al [ 29 ] Micro-CT assessment of first mandibular premolar was performed to analyze the root and canal morphology, accessory canals, intercanal communication, isthmus and apical foramina Teeth with mesial invaginations (27.8%) had multiple canals and majority of them were in the middle third of the root _ Vertcci’s classification: Type I: 65.2% Type III: 2.6% Type V: 22.6% Type VII: 0.9% 1–3-2: 2.6% 1–3: 5.2% 1–2-3: 0.9% Mesial invagination was present in 27.8% (32) of teeth, they were classified according to vertucci’s criteria as: Type I: 2 Type III: 2 Type V: 21 Type VII: 1 1–2-3: 1 1–3: 2 1–3-2: 3 Teeth with accessory canals were 35.7% Number of accessory canals: 1–87.8% 2–9.8 3–2.4% Location of accessory canals: Coronal: 0 Middle: 3 Apical: 38 Apical delta was seen in 6.1% of teeth _ Only 2 isthmuses were observed, one in the middle and the other in the apical third of teeth Loops were 8 in number, three in the middle and five in the apical third of specimen Out of the assessed teeth that showed the presence of RGACs, single foramen was seen in 74.6% of teeth at the groove, two foramina in 11.2% and three or more foramina in 14.3% of specimen. Their incidence was higher in the mid third of the root The average diameter of RGAC foramen was 0.088 ± 0.048, similarly average distance was 8.83 ± 2.53 from CEJP to FP at the groove Intercanal canal communication was recognized in 12% of sample teeth Micro-CT scanning of the mandibular first premolar among the included population revealed the complex morphology of the root with multiple canals and varied canal configurations Moreno, J.O., et al [ 30 ] Results analyzed canal configuration according to vertucci’s criteria and C shaped canals (1.8%) Mean values of parameters at 1,2 and 3 mm from apical foramen are as follows: Perimeter in mm: 1.07 ± 0.57, 1.27 ± 0.78 and 1.57 ± 0.84 Circulatory in mm: 0.59 ± 0.19, 0.57 ± 0.20 and 0.56 ± 0.22 Major diameter in mm: 0.41 ± 0.23, 0.48 ± 0.33 and 0.60 ± 0.37 ...…”
Section: Resultsmentioning
confidence: 96%
“…However, lingual view showed 73% of canals in the middle third and remaining in the coronal third In proximal view, mean angle α and β were 33.54∘ and 26.66∘ and angles were extremely curved while in the lingual view, they were less curved with mean angle α 8.31∘ and β 11.31∘ respectively _ _ _ _ _ _ _ The study provided the details of lingual canal, however the information obtained was influenced by the view used Liu, N., et al [ 29 ] Micro-CT assessment of first mandibular premolar was performed to analyze the root and canal morphology, accessory canals, intercanal communication, isthmus and apical foramina Teeth with mesial invaginations (27.8%) had multiple canals and majority of them were in the middle third of the root _ Vertcci’s classification: Type I: 65.2% Type III: 2.6% Type V: 22.6% Type VII: 0.9% 1–3-2: 2.6% 1–3: 5.2% 1–2-3: 0.9% Mesial invagination was present in 27.8% (32) of teeth, they were classified according to vertucci’s criteria as: Type I: 2 Type III: 2 Type V: 21 Type VII: 1 1–2-3: 1 1–3: 2 1–3-2: 3 Teeth with accessory canals were 35.7% Number of accessory canals: 1–87.8% 2–9.8 3–2.4% Location of accessory canals: Coronal: 0 Middle: 3 Apical: 38 Apical delta was seen in 6.1% of teeth _ Only 2 isthmuses were observed, one in the middle and the other in the apical third of teeth Loops were 8 in number, three in the middle and five in the apical third of specimen Out of the assessed teeth that showed the presence of RGACs, single foramen was seen in 74.6% of teeth at the groove, two foramina in 11.2% and three or more foramina in 14.3% of specimen. Their incidence was higher in the mid third of the root The average diameter of RGAC foramen was 0.088 ± 0.048, similarly average distance was 8.83 ± 2.53 from CEJP to FP at the groove Intercanal canal communication was recognized in 12% of sample teeth Micro-CT scanning of the mandibular first premolar among the included population revealed the complex morphology of the root with multiple canals and varied canal configurations Moreno, J.O., et al [ 30 ] Results analyzed canal configuration according to vertucci’s criteria and C shaped canals (1.8%) Mean values of parameters at 1,2 and 3 mm from apical foramen are as follows: Perimeter in mm: 1.07 ± 0.57, 1.27 ± 0.78 and 1.57 ± 0.84 Circulatory in mm: 0.59 ± 0.19, 0.57 ± 0.20 and 0.56 ± 0.22 Major diameter in mm: 0.41 ± 0.23, 0.48 ± 0.33 and 0.60 ± 0.37 ...…”
Section: Resultsmentioning
confidence: 96%
“…According to the Shannon-Nyquist theory, when 1/2 the size of the object was larger than the resolution of CBCT, the image of the object could be observed in CBCT [3] . And Moreno et al [22] reported a narrower diameter of 0.24 ± 0.10 mm at 3 mm from the root apex measured by Micro-CT (voxel size 17 μm), at which time some of the tiny root canals could not be easily distinguished, creating inaccuracies.…”
Section: Discussionmentioning
confidence: 99%
“…al. 32 , quienes evaluaron la circularidad y el diámetro mayor y menor de los 3 mm apicales de primeros premolares inferiores, observando un promedio de circularidad, a 3 mm del ápice, de 0.56 mm2, resultando el diámetro mayor 0.60 mm y menor 0.21 mm. En nuestro estudio, se observó un promedio del diámetro mayor de 1.40 mm y menor de 0.20 mm.…”
Section: Discussionunclassified
“…33 quienes analizaron la morfología de premolares inferiores con 3 conductos radiculares. La presencia de conductos ovalados dificulta la limpieza y conformación de los mismos, quedando áreas irregulares difíciles de alcanzar, con remanentes de tejido pulpar o debris residual contaminado, lo cual puede comprometer el éxito del tratamiento 32 . En nuestro estudio, a 3 mm del ápice, los conductos fueron ovales en un 14.36%, ovalados largos en un 1.22% y no se observó ningún conducto aplanado a este nivel.…”
Section: Discussionunclassified